A Quest on Successful Public Squares: The Case Study of Fountain Squares in Baku City - Dadashova, Jeyran (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
People may gather, trade, argue, vote, or simply spend time in public squares, which have traditionally been the heart of the city. For the last few decades, public spaces have seen significant changes, owing primarily to technical advancements that have resulted in the city's rapid growth. The public squares, like all other portions of the city, have been affected. Some of the squares became unsightly since they were no longer attractive and/or comfortable for the people. Moving from this argument, this study aims to uncover key features that have a favorable impact on the public square and make them successful entities. If an urban square can respond to people's requirements, make them feel at ease, it will be more appealing to wider public making it a successful urban space. For this purpose, the study focuses on key authors of urban design with an attempt to understand the key features that makes an urban space successful. These key features are reinforced in the selected examples from around the world. The knowledge gained from the literature based on successful urban squares are utilized to assess the fountain square in Baku city. Keywords: Features of Successful Public Square, Urban Spaces, Baku City, Sociability.

ÖZ: Geleneksel olarak kentin kalbi olarak tanımladığımız kamusal alanlar, insanların biraraya geldiği, alışveriş yaptığı, ve hoş vakit gecirdiği mekanlar olarak bilinmekte idi. Ancak son yarım yuzyıla baktığımızda, kentlerin ekonomik ve teknolojik dönüşümlere bağlı olarak nüfus hızla büyümüş; ve bu durum kamusal alanlar üzerinde de etkilerini göstermiştir. Dönüşümm geçiren kent meydanları eski işlevlerini yenilerine bırakırken, çekiciliklerini de yitirmişlerdir. Bu tartışmaden yola çıkan bu çalışma kentsel tasarım alanındaki ana kaynaklara ve seçilmiş başarılı örneklere yoğunlasarak kamusal alanlarda ön plana cikan temel kriterlere dikkat çekmeyi amaçlamaktadır. Insanlarin ihtiyaçlarına karşılık verebilen ve onlara belli bir konforu sunabilen meydanlar, tercih edilen başarılı mekanlar olarak kabul görmektedir. Bu kriterler ışığında Bakü kentindeki Çesme Meydanı’nı analiz eden çalışma, bu mekanın ne kadar başarılı olduğu konusunda bazı öngörülerde bulunmaktadır. Anahtar Kelimeler: Başarılı Meydanlar’ın Öğeleri, Kamusal Alanlar, Bakü Cesme Meydanı, Sosyal Yaşam.
Master of Science in Architecture. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2022. Supervisor: Asst. Prof. Dr. Pınar Uluçay Righelato.
Keywords: Architecture; Urban Design; Public Spaces; Plazas; Features of Successful Public Square; Urban Spaces; Baku City; Sociability